Rancang Bangun Prototipe Teknologi Persuasif Untuk Pengembangan Website Perpustakaan Berbasis Sistem Rekomendasi - Anantha, Miftah; Amin, Zaid (Jurnal Ilmiah Media Sisfo, 2025)
The development of information technology has brought significant changes to various sectors of life, including the world of libraries. With the rapid innovation in technology, various aspects of library services have now been transformed thru digitalization, enabling faster access to information. Nevertheless, many libraries still rely on non-digital lending systems. This research aims to design and develop a persuasive technology prototype for the Bina Darma University library website, integrating a Collaborative Filtering-based recommendation system to provide relevant book recommendations based on user preferences. The research methods used include usability testing and the Perceived Persuasiveness Questionnaire (PPQ) to evaluate the effectiveness and efficiency of the system. The research results show that the system prototype successfully improved effectiveness, with a success rate of 97.5%, efficiency of 88%, and a System Usability Scale (SUS) score of 79, indicating that the system is user-friendly and effective in changing user behavior toward technology-based book borrowing